2015
DOI: 10.1123/mc.2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Contributions of the Flexor Digitorum Brevis Muscle on Postural Stability

Abstract: Surprisingly little attention has been devoted to the role played by the intrinsic muscles of the human foot. The aim of this study was to quantify the capabilities of the flexor digitorum brevis (FDB) muscle to contribute to upright postural control. The approaches consisted of analysis of the effects of FDB contraction elicited by external electrical stimulation and quantification of the magnitude of FDB torque generation. The results showed the FDB can produce significant changes in static posture by itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In fact, plantar cutaneous afferents play a role in stabilizing the feet, providing an additional source of sensory input that enhances the detection of movement and controlling small‐ amplitude body sway (Kavounoudias et al, 1998, 1999). More particularly, some studies have suggested the role of toes in postural control (Okay and Kohn, 2015; Tanaka et al, 1996a, 1996b; Tortolero et al, 2008; Viseux et al, 2018). In order to maintain balance, toes are used to correct for postural disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, plantar cutaneous afferents play a role in stabilizing the feet, providing an additional source of sensory input that enhances the detection of movement and controlling small‐ amplitude body sway (Kavounoudias et al, 1998, 1999). More particularly, some studies have suggested the role of toes in postural control (Okay and Kohn, 2015; Tanaka et al, 1996a, 1996b; Tortolero et al, 2008; Viseux et al, 2018). In order to maintain balance, toes are used to correct for postural disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…The toes provide a stable surface area that remains in contact with the ground and serve to relay relevant sensory information to the central nervous system (Ku et al, 2012). Some authors (Okay and Kohn, 2015; Tortolero et al, 2008) showed that the toe muscle stimulation was capable of regulating CoP displacements, and may be a good candidate for controlling balance. In those studies, forward movement of the CoP was induced by different intensity of electrical stimulation applied to the toe muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These functions are also related to balance ability and walking. Okai et al reported that FDB has a vital contribution to postural control 24 ) . Moreover, Green and Brekke, and Hughes et al.…”
Section: Discussionmentioning
confidence: 99%
“…After skin preparation, self-adhesive bipolar electrodes were attached over foot muscles (FDB and AbH) ( Kelly et al, 2014 ; Okai & Kohn, 2015 ) and ankle muscles (TA, MG, LG and PL) in accordance with SENIAM recommendations ( Hermens et al, 2000 ). The electrodes were placed along the course of muscle fibers with a distance of two cm between the centers of electrodes.…”
Section: Methodsmentioning
confidence: 99%